THE FORMATION OF HEURISTIC THINKING OF MASTER'S IN CHOLAR CONDUCTING (METHODOLOGICAL ANALYSIS) - Цін, Сюй (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2020)
The article deals with the issue of innovative arrangement of the process of preparation of master's in pedagogical universities from the point of view of the heuristic approach to formation of creative personality of future teachers of conducting and choral disciplines. The urgent tasks of art education on creation of a new perfect system of professional training of specialists, search for heuristic mechanisms of filling the educational art process with new content are highlighted. Attention is drawn to the content of the preparation of masters in choral conducting as a concentrated creative process, which requires a detailed study of the possibilities of its heuristic ordering. The purpose of the article is to cover the methodological bases of forming the heuristic thinking of the master's in choral conducting of pedagogical universities. The research methods are applied – theoretical for the analysis of scientific researches in the field of educational philosophy, psychology of thinking, art education on the problem of forming heuristic thinking, conducted in Ukraine and abroad; general for comparison, systematization, generalization of scientific information from the standpoint of determining the methodological bases of the phenomenon under study. The concept of "heuristics" in the understanding of creativity of cognition, creativity of activity, productive thinking, creative search, achievement of new creative result is analyzed. The definition of "heuristic thinking" is considered as a creative intellectual activity aimed at finding ways to make decisions in the face of problematic situations to obtain a new product. The possibility of forming the heuristic thinking of master's in the course of conductor-choral training is substantiated. The basic functions of professional preparation of undergraduates (system, cognitive, prognostic, evaluative, projective, search, constructive) are presented. The basic approaches to the formation of the heuristic thinking of the undergraduate students in choral conducting: personal, hermeneutic, algorithmic, creative, acmeological, reflexive-activity. The results of the diagnostic stage of experimental work are presented. The basic directions of further research of the stated scientific problem are highlighted